Comparison of the sensitivity of different criteria to select lung cancer patients for screening in a cohort of German patients. (27th January 2023) - Walter, Julia; Kauffmann‐Guerrero, Diego; Muley, Thomas; Reck, Martin; Fuge, Jan; Günther, Andreas; Majeed, Raphael W.; Savai, Rajkumar; Koch, Ina; Dinkel, Julien; Schneider, Christian; Senghas, Karsten; et al.
Abstract: Introduction: Trials of CT‐based screening for lung cancer have shown a mortality advantage for screening in North America and Europe. Before introducing a nationwide lung cancer screening program in Germany, it is important to assess the criteria used in international trials in the German population. Methods: We used data from 3623 lung cancer patients from the data warehouse of the German Center for Lung Research (DZL). We compared the sensitivity of the following lung cancer screening criteria overall and stratified by age and histology: the National Lung Screening Trial (NLST), the Danish Lung Cancer Screening Trial (DLCST), the 2013 and 2021 US Preventive Services Task Force (USPSTF), and an adapted version of the Prostate, Lung, Colorectal, and Ovarian no race model (adapted PLCOm2012) with 6‐year risk thresholds of 1.0%/6 year and 1.7%/6 year. Results: Overall, the adapted PLCOm2012 model (1%/6 years), selected the highest proportion of lung cancer patients for screening (72.4%), followed by the 2021 USPSTF (70.0%), the adapted PLCOm2012 (1.7%/6 year) (57.4%), the 2013 USPTF (57.0%), DLCST criteria (48.7%), and the NLST (48.5%). The adapted PLCOm2012 risk model (1.0%/6 year) had the highest sensitivity for all histological types except for small‐cell and large‐cell carcinomas (non‐significant), whereas the 2021 USPTF selected a higher proportion of patients. The sensitivity levels were higher in males than in females. Conclusion: Using a risk‐based selection score resulted in higher sensitivities compared to criteria using dichotomized age and smoking history. However, gender disparities were apparent in all studied eligibility criteria. In light of increasing lung cancer incidences in women, all selection criteria should be reviewed for ways to close this gender gap, especially when implementing a large‐scale lung cancer screening program. Abstract : A comparison of lung cancer screening selection approaches resulted in higher sensitivities in risk‐based models compared to criteria using dichotomized categorical age and smoking history in a German population of lung cancer patients. However, gender disparities were apparent in all studied eligibility criteria. In light of increasing lung cancer incidences in women, all selection criteria should be reviewed regarding ways to close this gender gap, especially when implementing a large‐scale lung cancer screening program.